The Effects of Sodium-Glucose Cotransporter 2 Inhibitors on Sympathetic Nervous Activity - Wan, Ningning; Rahman, Asadur; Hitomi, Hirofumi; Nishiyama, Akira (Frontiers in Endocrinology, 2018)
The EMPA-REG OUTCOME study revealed that a sodium-glucose cotransporter 2 (SGLT2) inhibitor, empagliflozin, can remarkably reduce cardiovascular (CV) mortality and heart failure in patients with high-risk type 2 diabetes. Recently, the CANVAS program also showed that canagliflozin, another SGLT2 inhibitor, induces a lower risk of CV events. However, the precise mechanism by which an SGLT2 inhibitor elicits CV protective effects is still unclear. Possible sympathoinhibitory effects of SGLT2 inhibitor have been suggested, as significant blood pressure (BP) reduction, following treatment with an SGLT2 inhibitor, did not induce compensatory changes in heart rate (HR). We have begun to characterize the effects of SGLT2 inhibitor on BP and sympathetic nervous activity (SNA) in salt-treated obese and metabolic syndrome rats, who develop hypertension with an abnormal circadian rhythm of BP, a non-dipper type of hypertension, and do not exhibit a circadian rhythm of SNA. Treatment with SGLT2 inhibitors significantly decreased BP and normalized circadian rhythms of both BP and SNA, but did not change HR; this treatment was also associated with an increase in urinary sodium excretion. Taken together, these data suggest that an SGLT2 inhibitor decreases BP by normalizing the circadian rhythms of BP and SNA, which may be the source of its beneficial effects on CV outcome in high-risk patients with type 2 diabetes. In this review, we briefly summarize the effects of SGLT2 inhibitors on BP and HR, with a special emphasis on SNA.